2017
DOI: 10.1016/j.stemcr.2017.04.013
|View full text |Cite
|
Sign up to set email alerts
|

NEUROD1 Instructs Neuronal Conversion in Non-Reactive Astrocytes

Abstract: SummaryCurrently, all methods for converting non-neuronal cells into neurons involve injury to the brain; however, whether neuronal transdifferentiation can occur long after the period of insult remains largely unknown. Here, we use the transcription factor NEUROD1, previously shown to convert reactive glial cells to neurons in the cortex, to determine whether astrocyte-to-neuron transdifferentiation can occur under physiological conditions. We utilized adeno-associated virus 9 (AAV9), which crosses the blood-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(83 citation statements)
references
References 38 publications
4
78
0
1
Order By: Relevance
“…We first established mouse astrocytes in vitro and cultured them without growth factors ( Figure S5A), a condition under which they display properties closely resembling those of non-reactive astrocytes in the physiological state (White et al, 2011). In accordance with our earlier findings (Brulet et al, 2017), we observed few Map2ab-positive cells in ND1-transduced non-reactive astrocytes at 7 dpt ( Figures S5B and S5C). This result is in marked contrast to a previous study in which astrocytes were grown in the presence of epidermal growth factor (EGF) and fibroblast Figure 3.…”
Section: Nd1 Occupies Bivalent Domains and Induces Neuronal Reprogramsupporting
confidence: 88%
See 3 more Smart Citations
“…We first established mouse astrocytes in vitro and cultured them without growth factors ( Figure S5A), a condition under which they display properties closely resembling those of non-reactive astrocytes in the physiological state (White et al, 2011). In accordance with our earlier findings (Brulet et al, 2017), we observed few Map2ab-positive cells in ND1-transduced non-reactive astrocytes at 7 dpt ( Figures S5B and S5C). This result is in marked contrast to a previous study in which astrocytes were grown in the presence of epidermal growth factor (EGF) and fibroblast Figure 3.…”
Section: Nd1 Occupies Bivalent Domains and Induces Neuronal Reprogramsupporting
confidence: 88%
“…These findings suggest that ND1 instructs reprogramming of the epigenetic landscape to silence microglial cell identity. Because ND1 does not always effectively induce neuronal reprogramming in cells such as non-reactive astrocytes (Brulet et al, 2017), we believe that future studies (e.g., stepwise analysis of the epigenetic profile and chromatin modifier dynamics during neuronal reprogramming from different types of somatic cells) will yield insights into how and when ND1 achieves the rewriting of the epigenetic landscape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since certain serotypes of AAV can cross the blood-brain-barrier (BBB), intravenous delivery of conversion factors has make it possible to reach a broader area of the CNS (Chan et al, 2017;Foust et al, 2009). Following our earlier report of efficient conversion of reactive astrocytes into functional neurons by NeuroD1 through retroviral infection (Guo et al, 2014), intravenous injection of AAV9 expressing NeuroD1 has been reported to infect a small but significant number of resting astrocytes in the striatum and convert them into neurons (Brulet et al, 2017). On the other hand, our intracranial injection of AAV9 expressing NeuroD1 in stab injury model (Zhang et al, 2018) and ischemic injury model (Chen et al, 2018) have both resulted in high conversion efficiency, suggesting that reactive astrocytes are more likely converted into neurons than the resting astrocytes.…”
Section: Aav Gene Delivery System For Neuronal Conversionmentioning
confidence: 89%